FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK (Studi Pada UKM Di Kecamatan Gayamsari) - Sheila Adelina, 11.05.52.0200; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2015)
One of the biggest state revenue to support the countrys life is taxes. Tax compliance is one of the factors that affect the size of a state income tax. This study aimed to examine the effect of tax knowledge, tax awareness, quality of service tax authorities, tax rates, and tax penalties on tax compliance SMEs. The population in this study is the taxpayer SMEs in Gayamsari, Semarang City as much as 80 SMEs that are in 7 villages namely, Gayamari, Tambakrejo, Kaligawe, large rice fields, Siwalan, Tendean Lamper, Sambirejo. The sampling method is done by census sampling method, the number of taxpayers SME population in Sub Gayamsari entirely used as a sample in the study. The analysis tool used is multiple linear regression. The results showed that knowledge of tax significant positive effect on the SME tax compliance, tax awareness significant positive effect on the SME tax compliance, service quality fiskus significant positive effect on the SME tax compliance, tax rates significant positive effect on the taxpayer kepatuhaan SMEs, and tax penalties significant positive effect on the SME.Keywords: Knowledge Tax, Tax Awareness, Service Quality Authorities, Tax Rate, Tax Sanctions, Taxpayer Compliance SMEs